Qualitatively Comparing the Support Needs of People with Cancer Based on Their History of Anxiety/Depression - Richardson, Emma M. (Oncol Ther, 2017)
INTRODUCTION: Research rarely considers the origin or history of a cancer patient’s anxiety and/or depression, instead assuming that these illnesses are related to the cancer experience. The aim of this study was to compare differences in the support needs of people who have experienced anxiety/depression as part of the cancer experience and people who have not, as well as between people who have experienced episodic anxiety/depression and people who have experienced long-term anxiety/depression. METHODS: Twenty-one semi-structured interviews were conducted with people with a current or previous diagnosis of cancer, and a current or previous experience with anxiety and/or depression. Participants were split into four groups based on their history with cancer and anxiety/depression, and an inductive thematic analysis was conducted to identify themes across groups. RESULTS: Two superordinate themes (with three and two subordinate themes respectively) were found: ‘coping with cancer’ and ‘health care system support provision’. Important differences were found across groups, with participants who had a history of anxiety/depression that was unrelated to their cancer diagnosis coping better with the combined burden of cancer and anxiety/depression, experiencing less fear of cancer recurrence, and highlighting more positive hospital and support service related experiences, than those whose anxiety/depression was cancer related. CONCLUSION: The origin and history of a person’s anxiety/depression is important to consider when determining how they might cope with cancer, what their support needs are, and how much support they may require. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40487-017-0045-3) contains supplementary material, which is available to authorized users.